Eco-NIOKR LLC – 18 years for the protection of birds at the electric grid facilities of the Russia - Igor A. Panov (Пернатые хищники и их охрана)
We have been developing and manufacturing special bird protection devices (SBPD) for overhead power lines (PL) and substations since 2006. Our devices are in demand all over Russia, from Kaliningrad to Khabarovsk. Products are developed by experienced designers with the participation of ornithologists – professional experts in bird protection. The combined experience of specialists allows us to produce effective, reliable, and durable SBPDs. Today the company owns 23 patents.